Comparative Analysis for Helical Spring and Belleville Spring Used in Aerosol Container Valve - Modh, Mehul (Asian Review of Mechanical Engineering, 2012)
Aerosol is to spray in fine particles from pressurized fluid. It is widely used in insect killer room freshener as well as perfumes. Various designs of such products are available and they are based on ergonomically as well as aesthetical consideration. In this paper, same consideration is used, model is made in Pro-e software and analysis is made in ANSYS software to justify the answer. Here, two different springs like Belleville as well as Conventional spring called “Helical Spring”. Due to application of same load on Belleville as well as helical spring, a graph of load versus deflection is produced. The objective of this work is to prevent the leakage as well as less pressure or effort application on valve of the aerosol container to spray the contains.